KEANEKARAGAMAN KUPU-KUPU DI DESA SANGEH, KABUPATEN BADUNG, PROVINSI BALII - Dinata, Anak Agung Ngurah Bagus Adi Permana; Dalem, A.A.Gde Raka; Suartini, Ni Made Made (SIMBIOSIS, 2023)
Butterflies have a biological function that can be used as a bioindicator of health assessment in an environment. This is because butterflies are insects or organisms that are very sensitive to changes in an environment so they are suitable as a study of conservation biology studies. The purpose of this study was to determine the type or diversity of butterflies in Sangeh Village. Butterfly sample data collection was carried out using the roaming method and was carried out for 3 months. Butterfly sampling was carried out on 8 lines called stations and sampling was repeated 4 times. Butterfly identification was carried out in two ways, namely in situ (at the research site) and ex-situ (outside the research location). The results of the research in Sangeh Village found 41 types of butterflies. The results of calculating the diversity index of butterflies at all stations were 3.18 with the highest diversity index at station II (3.02), while the lowest was at station VI (2.54).